A key to species of Hercinothrips, with one new species, and a neotype designation for H. trilineatus (Priesner) - Goldaracena, Arturo; Vierbergen, Gijsbertus (Bert) (Zootaxa, 2022)
A female neotype from Transvaal, South Africa, is designated for Hercothrips trilineatus Priesner, the original type specimens from Tanzania having been destroyed in Hamburg during the 1940’s. Hercinothrips splendens sp.n. is described from both sexes taken from Aloe plants in a Netherlands greenhouse. A key is provided to the 10 known extant species of Hercinothrips.